The potash market and its future prospects. (March 2016) - Rawashdeh, Rami Al; Xavier-Oliveira, Emanuel; Maxwell, Philip
Abstract: The purpose of the paper was to assess the main historical drivers of potash demand, to generate estimates of demand elasticities and to produce forecasts of potash consumption during the coming decade. The paper has used a comprehensive econometric model to estimate shortrun and long run price, income and cross elasticities. The world potash demand is found to be price inelastic in the short-run and even in the long run. Also, income, cross price elasticity and cross yield elasticity were found to be inelastic in the short and long run. Our modeling predicts that potash consumption for fertilizers will increase from 28.2 million tonnes in 2012 to around 37.8 million tonnes in 2022, which implies that the annual relative growth rate of potash consumption is expected to increase by 2.9%. As long as demand increases our prediction is that real potash prices will also increase, ceteris paribus. Delays in commissioning new production capacity are likely the main reason for price increases. Yet additional planned capacities that could potentially take place in the next decade still have the potential to limit the upside for potash prices. Highlights: World potash demand is price inelastic in the short-run and even in the long run. Income elasticity, cross price elasticity and cross yield elasticity are inelastic in the short-run and the long run. Our modeling predicts that potash consumption for fertilizers will increase from 28.2 million tonnes in 2012 to around 37.8 million tonnes in 2022. As long as demand increases our prediction is that real potash prices will also increase, ceteris paribus .